Using temporal relations to specify and test an instant messaging server - Hughes, John; Norell, Ulf; Sautret, J. (Proceedings - International Conference on Software Engineering, 2010)
Asynchronous events are awkward to handle in specification-based testing. State machine specifications become very complex when variable event order, timing constraints, and timing uncertainties must all be captured. We propose an alternative formalism for specifying asynchronous behaviour based on temporal relations, designed to support more declarative and modular specifications. Temporal relations are in a sense a combination of bulk data types and temporal logic. We illustrate the formalism by specifying parts of a simplified instant messaging server, and show that it can handle timing uncertainty very simply. We have implemented the formalism as part of Quviq QuickCheck, a commercial specification-based testing tool, and we describe its application to testing ejabberd, the leading instant messaging server based on the open XMPP protocol. Copyright 2010 ACM.